2012
DOI: 10.1007/s11999-011-1830-1
|View full text |Cite
|
Sign up to set email alerts
|

Is Percutaneous Repair Better Than Open Repair in Acute Achilles Tendon Rupture?

Abstract: Background Open repair of Achilles tendon rupture has been associated with higher levels of wound complications than those associated with percutaneous repair. However, some studies suggest there are higher rerupture rates and sural nerve injuries with percutaneous repair. Questions/purposesWe compared the two types of repairs in terms of (1) function (muscle strength, ankle ROM, calf and ankle perimeter, single heel rise tests, and work return), (2) cosmesis (length scar, cosmetic appearance), and (3) complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
83
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 25 publications
6
83
0
8
Order By: Relevance
“…In 2012, Diao et al [71] reported favorable short-term clinical outcomes using the Achillon device (Integra, Plainsboro, NJ). Similar favorable findings were demonstrated in numerous other studies [72][73][74][75] with regard to functional outcome, better cosmetic appearance, less wound complications, patient satisfaction, and imaging results using percutaneous techniques (Fig. 2).…”
Section: Percutaneous Techniquessupporting
confidence: 89%
“…In 2012, Diao et al [71] reported favorable short-term clinical outcomes using the Achillon device (Integra, Plainsboro, NJ). Similar favorable findings were demonstrated in numerous other studies [72][73][74][75] with regard to functional outcome, better cosmetic appearance, less wound complications, patient satisfaction, and imaging results using percutaneous techniques (Fig. 2).…”
Section: Percutaneous Techniquessupporting
confidence: 89%
“…2 After patients adopted the testing position, they performed 3 maximal attempts guided by pain perception of equal to or less than 8 of 10 during each evaluation. Pain perception was determined using a verbal analogue scale, ranging from 0 (absence of pain) to 10 (maximal pain).…”
Section: Isometric Pfsmentioning
confidence: 99%
“…A n Achilles tendon (AT) rupture is the most frequent tendon injury in the lower limb, with an incidence of 18 per 100 000 individuals each year, [1][2][3][4][5] most of whom are middle-aged [5][6][7] male amateur athletes. 1,8 Tendinous overload 6,9 and a nonuniform distribution of stress 10 promoted by neuromuscular imbalance 11 or pathologic muscular conditions 12 are mechanical factors that contribute to an AT rupture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They occur more commonly in men in the third or fourth decade. Due to increasing of sport activities in the population there is an increase in sports injuries and also in AT ruptures [1,2].…”
mentioning
confidence: 99%